Design of Power Generating Speed Breakers - Aditya Sinha, Shasank Mittal, Abhishek Jakhmola, Sujeet Kumar Mishra (International Journal of Advanced Science and Technology, 2020)
This paper presents an innovative and sustainable method of energy production from the massive chunk of energy which is wasted when a vehicle passes over speed breakers. The central idea is to design a speed breaker assembly that generates electricity in order to operate roadways accessories such as street lights, traffic signals, etc. The reciprocation of the speed breaker - under the weight of a vehicle - is converted into rotary motion using slider-crank mechanism. This rotation is transmitted to the pinion of a generator using gear drive thus generating electricity. A restoring spring-damper mechanism is used to drive the speed breaker back to its original position. The power generated depends on parameters like frequency of vehicles passing over the speed breaker, the velocity and the mass of the vehicles. The design is economical and easy to install on busy roadways. With proper adaptations, the design may also be incorporated under railway tracks.